Al-Al’āb Al-Mushammamah Li Ta’līmi Al-Lughah Al-Arabiyyah Bi Al-Kalimāt Al-Indūnīsiyyah Dzāt Asl ‘Arabī Fī Mu’jam Al Lughah Al Indunisiyyah - Nailatun Nahdhah; Kristiana (Mauriduna: Journal of Islamic Studies, 2020)
هدفت هذه الدراسة إلى تصميم الألعاب اللغوية المناسبة لتعليم اللغة العربية من خلال الكلمات الإندونيسية ذات أصل عربي، نظرا لقلة وعي معلمي اللغة العربية بكيفية تعليم اللغة العربية الجيدة، وبالتالي يشكل في أذهان المتعلمين أن دراسة اللغة العربية صعبة ومملة. والمنهج الذي سلكته الباحثة في إنجاز هذه الدراسة هو منهج الوصف التحليلي. ومرت الباحثة في تصميم هذه الألعاب بعدة مراحل، وهي التخطيط، التصميم، التنفيذ والتقويم. وفي مرحلة التصميم بينت الباحثة عملية التصميم من حيث هدف اللعبة، قواعد اللعبة، المهارة المستهدفة من اللعبة، وكذا كيفية تنفيذها. ففي هذا البحث صممت الباحثة 8 الألعاب اللغوية المناسبة لتعليم اللغة العربية من خلال الكلمات الإندونيسية ذات أصل عربي واستخدمت فيها 61 المفردات الإندونيسية ذات أصل عربي. ولمعرفة صلاحية هذه الألعاب، طبقت الباحثة الألعاب على 50 عينة من 146 طالبات المستوى الإعدادي بجامعة الراية وتوصلت إلى النتيجة الآتية: أن 8 الألعاب المصممة مناسبة لتعليم اللغة العربية ويدخل فيها تعليم المهارات الأربع، حيث أن النسبة المئوية بعد قيام بتطبقها وتوزيع الاستبانة "93،4%"، و وهذا يدل على أن الألعاب المصممة مناسبة في لتعليم اللغة العربية من خلال بعض الكلمات الإندونيسية ذات أصل عربي و وتؤثر فيها تأثيرا إيجابيا. This study aims to design language games that are suitable for teaching Arabic through Absorption Words in the Dictionary KBBI, due to the lack of understanding of Arabic language teachers about good and creative teaching methods, giving rise to the impression that learning Arabic is difficult and boring. Therefore, the design of language games can help Arabic teachers in developing and providing variations in their teaching. The method used in this research is descriptive analysis method. And in order to design a game, the writer goes through several stages, namely planning, design, practice and evaluation. In the design phase, the writer explains in detail the game design, both in terms of the objective of the game, the rules of the game, and also how to implement or apply the game. In this research, the researcher designed 8 suitable games to teach the Arabic language trough Indonesian vocabulary of Arabic origin and used 96 indonesian vocabulary words of Arabic origin. To find out the validity of these games, the games were applied to 50 students from Arraayah university’s preparation department. And the application reached that the conclusion that the games are suitable for the Arabic teaching, as the percentage after the application and resolution is 85,4% for those who have decided to benefit from them, and this indicates that these games are suitable for Arabic teaching.